Anin vitroFcRn- dependent transcytosis assay as a screening tool for predictive assessment of nonspecific clearance of antibody therapeutics in humans - Shan Chung; Nguyễn Văn Hiệp; Yuwen Linda Lin; Julien Lafrance‐Vanasse; Suzie J. Scales; Kevin Lin; Rong Deng; Kathi Williams; Gizette Sperinde; Juan Jenny Li; Kai Zheng; Siddharth Sukumaran; et al. (2019)
A cell-based assay employing Madin–Darby canine kidney cells stably expressing human neonatal Fc receptor (FcRn) heavy chain and β2-microglobulin genes was developed to measure transcytosis of monoclonal antibodies (mAbs) under conditions relevant to the FcRn-mediated immunoglobulin G (IgG) salvage pathway. The FcRn-dependent transcytosis assay is modeled to reflect combined effects of nonspecific interactions between mAbs and cells, cellular uptake via pinocytosis, pH-dependent interactions with FcRn, and dynamics of intracellular trafficking and sorting mechanisms. Evaluation of 53 mAbs, including 30 marketed mAb drugs, revealed a notable correlation between the transcytosis readouts and clearance in humans. FcRn was required to promote efficient transcytosis of mAbs and contributed directly to the observed correlation. Furthermore, the transcytosis assay correctly predicted rank order of clearance of glycosylation and Fv charge variants of Fc-containing proteins. These results strongly support the utility of this assay as a cost-effective and animal-sparing screening tool for evaluation of mAb-based drug candidates during lead selection, optimization, and process development for desired pharmacokinetic properties.